Perfil de sensibilidade de cepas planctônicas e biofilmes de enterococcus faecalis frente a desafios antimicrobianos - Arruda, Theodora Thays Prado (2007)
Enterococcus faecalis has been suggested to be an important etiological agent in endodontic failure. It has been found in the root canal system in a perceptual ranging from 22% to 77% and it has been associated to organisms structured in biofilms. The aim of the present study was to evaluate, in vitro, the effectiveness of endodontic sealers, 2.5% sodium hypochlorite, and 0.5% Lippia sidoides essential oil in eliminating E. faecalis biofilms. Clinical material was collected from 37 patients with root canal chronic infections and 14 Enterococcus faecalis strains were isolated (37.8%). Biofilms from a reference (ATCC) and a clinical multirresistant strain (isolate 12 ) were grown for 8 days. This period was selected based on a chronological study of the Enterococcus faecalis biofilm development through Atomic Force Microscopy. It was verified that there was a significant reduction of the bacteria number when the biofilms were exposed to the endodontic sealers related to the control for the two tested strains (p<0.001). Analyzing the ATCC strain, it was seen that the Epiphany® endodontic sealer presented similar action compared to Endofill® (p>0.05), similar result was found for Isolate 12. When the strains susceptibilities against the sealers was compared it was verified that the isolate 12 was less susceptible than the ATCC strain (p<0.001). It was verified that the 0.5% essential oil solution of Lippia siodides presented a similar action to 2.5% sodium hypochlorite when the biofilm of ATCC strain and isolate 12 were exposed for 10 minutes to this substances (p<0.001). Comparing the susceptibility of the two strains to the solutions tested, there was no difference between them (p>0.05)